OPTIMALISASI CITRA MEREK DAN DIFERENSIASI PRODUK DALAM MENUMBUHKAN LOYALITAS KONSUMEN (PRODUK MAKANAN KECIL TUM TIM DI SIDOARJO) - Muhafidhah Novie (Universitas Nahdlatul Ulama Sidoarjo, 2020)
The purpose of this study is to calculate the magnitude of (1) the impact of brand image in fostering consumer loyalty, a study on the Tum Team cake (2) the impact of product differentiation in fostering consumer loyalty. big on consumer loyalty. This study determined a sample of 33 customers of the Tum Tim cake. The quantitative approach research method is used in this study, using statistical tools using the SPSS 22 application, as an analysis tool. On the basis of the analysis suggests that (1) brand image is able to improve the performance of new products (2) product differentiation has an effect on increasing the level of consumer loyalty (3) Analysis of the multiple linear regression equation implies that brand image fosters a stronger impact than product differentiation to grow the level of consumer loyalty Tum Tim.